A
b
x−c=0
Step 1: Multiply both sides by b.
ax−bc=0
Step 2: Add bc to both sides.
ax−bc+bc=0+bc
ax=bc
Step 3: Divide both sides by x.
ax
x
=
bc
x
a=
bc
x
Answer:
a=
bc
x
S = sally C = Chris J = Joe
sally is one year older than 3 times the age of joe, so
s = 3j + 1
chris is 5 years younger than 6 times the age of jo, so
c = 6j - 5
sally and chris are the same age so
s = c so
3j + 1 = 6j - 5
-3j -3j
1 = 3j - 5
+5 +5
6 = 3j or
3j = 6
3j/3 = 6/3
j = 2
check
s = c
3(2) +1 = 6(2) - 5
6 + 1 = 12 - 5
7 = 7 correct✅
Answer:
64
Step-by-step explanation:
Answer:
Z.
Step-by-step explanation:
I wrote down the subject with the number of students. I looked one by one to see if the number of students with the subject matched with the graph. Then I finally found that the last graph matched with what I written down.
Answer: 26
Step-by-step explanation:
32-6 = 26